Motor Adaptation in Parkinson’s Disease During Prolonged Walking in Response to Corrective Acoustic Messages - Corzani, Mattia; Ferrari, Alberto; Ginis, Pieter; Nieuwboer, Alice; Chiari, Lorenzo (Frontiers in Aging Neuroscience, 2019)
Wearable sensing technology is a new way to deliver corrective feedback. It is highly applicable to gait rehabilitation for persons with Parkinson’s disease (PD) because feedback potentially engages spared neural function. Our study characterizes participants’ motor adaptation to feedback signaling a deviation from their normal cadence during prolonged walking, providing insight into possible novel therapeutic devices for gait re-training. Twenty-eight persons with PD (15 with freezing, 13 without) and 13 age-matched healthy elderly (HE) walked for two 30-min sessions. When their cadence varied, they heard either intelligent cueing (IntCue: bouts of ten beats indicating normal cadence) or intelligent feedback (IntFB: verbal instruction to increase or decrease cadence). We created a model that compares the effectiveness of the two conditions by quantifying the number of steps needed to return to the target cadence for every deviation. The model fits the short-term motor responses to the external step inputs (collected with wearable sensors). For the 90th-percentile values only, motor adaptation during IntFB was significantly faster than during IntCue among all participants when cadence had to increase (p value = 0.048). During IntFB both groups adapted similarly during the first steps of exposure to both increasing and decreasing inputs. Increasing rather than decreasing the pace appeared to be more difficult for both groups. In fact, under IntFB the PD group required about seven steps to increase their cadence, whereas they only needed about three steps to decrease their cadence. However, this difference was not significant; perhaps future work could include more participants and/or more sessions, increasing the total number of deviations for analysis. Notably, a significant negative correlation, r = -0.57 (p value = 0.008), was found between speed of adaptation and number of deviations during IntCue, but not during IntFB—suggesting that, for people who struggle with gait, such as those with PD, verbal instructions rather than metronome beats may be more effective at restoring normal cadence. Clinicians and biofeedback developers designing novel therapeutic devices could apply our findings to determine the optimal timing for corrective feedback, optimizing gait rehabilitation while minimizing the risk of cue-dependency.